2011
DOI: 10.1002/sia.3565
|View full text |Cite
|
Sign up to set email alerts
|

Application of TOF‐SIMS to the direct determination of syringyl to guaiacyl (S/G) ratio of lignin

Abstract: The lignin syringyl to guaiacyl (S/G) ratio, the composition of monomeric units, is an important parameter that is widely used to obtain information on the complex polymer structure of lignin present in plant cell walls. We assessed the reliability of time-of-flight secondary ion mass spectrometry (TOF-SIMS) for determining the S/G ratio using monomer, dimer and polymer model compounds of lignin. In the case of the monomer and dimer, the S/G ratios were much higher than the actual molar S/G ratios. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…These products were identified by FT-ICR-MS as 4-hydroxy benzaldehyde (H′), vanillin (G′), and syringaldehyde (S′), respectively, then confirmed by comparison of their retention times and MS/MS spectra with pure standards (Sigma-Aldrich). This result is in accordance with a previous study analyzing the monolignols by direct ionization (without previous hydrolysis of lignin, possibly ionizing the soluble monomers and oligomers as well) that indicated m/z 151 (C 8 H 7 O 3 ) as one of the ions formed by the TOF-SIMS analysis of the G monomer and m/z 181 (C 9 H 9 O 4 ) of the S monomer [1]. Lima et al (2008) also identified vanillin (G′) as one of the main products of the nitrobenzene oxidation of G and syringaldehyde (S′) as a product of S [19].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These products were identified by FT-ICR-MS as 4-hydroxy benzaldehyde (H′), vanillin (G′), and syringaldehyde (S′), respectively, then confirmed by comparison of their retention times and MS/MS spectra with pure standards (Sigma-Aldrich). This result is in accordance with a previous study analyzing the monolignols by direct ionization (without previous hydrolysis of lignin, possibly ionizing the soluble monomers and oligomers as well) that indicated m/z 151 (C 8 H 7 O 3 ) as one of the ions formed by the TOF-SIMS analysis of the G monomer and m/z 181 (C 9 H 9 O 4 ) of the S monomer [1]. Lima et al (2008) also identified vanillin (G′) as one of the main products of the nitrobenzene oxidation of G and syringaldehyde (S′) as a product of S [19].…”
Section: Resultssupporting
confidence: 94%
“…Lignin is a complex phenolic polymer which plays an important role in the mechanical support and permeability of plants, as well as the resistance to microbial degradation of plant tissues [1]. It is composed primarily of three monomeric units commonly denominated by guaiacyl (G) derived from coniferyl alcohol, syringyl (S) derived from sinapyl alcohol, and p-hydroxyphenyl (H) derived from coumaryl alcohol (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…When obtaining quantitative information using TOF‐SIMS, the difference in the ionization efficiencies between compounds should be noted. In a recent report (Saito et al. , 2011), we showed that the S and G monomeric ions can be ionized with similar efficiencies using an equimolar mixture of 8‐O‐4′–linked polymer models of S and G types.…”
Section: Discussionmentioning
confidence: 74%
“…Saito et al (2011) demonstrated that the S/G value for a β-O-4′ type polymer is in good agreement with the molar ratio of the units. S/G values of a maple tree obtained from thioacidolysis and TOF-SIMS were dependent from the situation of the annual rings within the stem , however, the S/G value obtained by TOF-SIMS are lower than those evaluated by thioacidolysis because all chemical degradation (Nakashima et al 2008;Zheng et al 2014b).…”
Section: Evaluation Of Tof-sims Datamentioning
confidence: 54%
“…The S/G data can be evaluated by TOF-SIMS (Saito et al 2011Zhou et al 2011). Saito et al (2011) demonstrated that the S/G value for a β-O-4′ type polymer is in good agreement with the molar ratio of the units.…”
Section: Evaluation Of Tof-sims Datamentioning
confidence: 96%